2010
DOI: 10.1093/ndt/gfq343
|View full text |Cite
|
Sign up to set email alerts
|

The time course of peritoneal transport parameters in peritoneal dialysis patients who develop encapsulating peritoneal sclerosis

Abstract: The risk of EPS increases with continuation of PD while UFF is present. Transport characteristics are similar between EPS patients and UFF patients without this complication. A constantly low ELAR may distinguish the EPS patients from those with UFF only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
58
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 20 publications
3
58
0
5
Order By: Relevance
“…These results are in line with those from an uncontrolled Dutch cohort showing that patients with EPS had a progressive decline in UF capacity over 4 years and an inverse U-shaped trend in small solute transport. 21 The use of time-matched controls in a UK cohort showed a clear difference in UF capacity between patients with EPS and controls at least 2 years before PD withdrawal. 14 However, the latter study, based on 2.27% glucose PET, could not assess free-water transport.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results are in line with those from an uncontrolled Dutch cohort showing that patients with EPS had a progressive decline in UF capacity over 4 years and an inverse U-shaped trend in small solute transport. 21 The use of time-matched controls in a UK cohort showed a clear difference in UF capacity between patients with EPS and controls at least 2 years before PD withdrawal. 14 However, the latter study, based on 2.27% glucose PET, could not assess free-water transport.…”
Section: Discussionmentioning
confidence: 99%
“…Preliminary studies suggested that a progressive loss of UF capacity often precedes EPS development. 14,15 However, these studies were limited by small numbers, the absence of appropriate matching with long-term PD controls, and/or a lack of evaluation of free-water transport. In addition, the mechanisms of impaired water transport in patients with EPS have not been investigated and remain unelucidated.…”
mentioning
confidence: 99%
“…Patients who develop EPS have been shown to have higher peritoneal transport rates and lower net ultrafiltration compared with matched control patients (Hendriks et al 1997) but peritoneal transport characteristics were not available in this study. It has been reported that patients with ultrafiltration failure, defined as net ultrafiltration less than 400ml after a 4 hour dwell time using 3.86% dialysis fluid, are at high risk of developing EPS if PD is continued (Sampimon et al 2011). In this recent study half of the patients with ultrafiltration failure who remained on PD for more than 3 years developed EPS (Sampimon et al 2011).…”
mentioning
confidence: 84%
“…It has been reported that patients with ultrafiltration failure, defined as net ultrafiltration less than 400ml after a 4 hour dwell time using 3.86% dialysis fluid, are at high risk of developing EPS if PD is continued (Sampimon et al 2011). In this recent study half of the patients with ultrafiltration failure who remained on PD for more than 3 years developed EPS (Sampimon et al 2011).…”
mentioning
confidence: 84%
“…[6][7][8] The lymphatic absorption rate, which is measured by the rate at which intraperitoneally administered radioactive serum albumin or the macromolecule dextran 70 disappears, is significantly higher in patients with ultrafiltration failure, and lymphatic absorption is considered to be one of the causes of the decrease in net ultrafiltration. [9][10][11][12] However, the results from these clinical approaches have been controversial, 13,14 and there are no other methods available to assess lymphatic function.…”
mentioning
confidence: 99%